The artistic polyvalence of the legendarily-mythological image: the factors of the analysis (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
In this article the parameters of the artistic polyvalence of the legendarily-mythological image are specified. That polyvalence is the key factor in the mechanism of isomorphism of traditional structures and it is an important one in their (vertical) analysis of the systems. The proper terminology is offered, the functional description of the mediated artistic valency of traditional structure is realized for the first time. The chart of exposure of the amplitude of the legendarily-mythological structures interpretation is generalized on the example of popular in literature of the beginning of the XXI century interpretations metatexts of the images of the Unicorn and Minotaur.
Keywords: artistic polyvalence; metatext; amplitude of interpretation; legendarily-mythological structure; analyses; image; installation